1999
DOI: 10.1177/00131649921970206
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory Factor Analysis of the Chinese Version of the Motivated Strategies for Learning Questionnaire

Abstract: Confirmatory factor analysis was used to evaluate the factor structure of a Chinese version of Pintrich and De Groot’s Motivated Strategies for Learning Questionnaire (MSLQ). Data were gathered from a sample of 477 junior high and high school students, ranging in age from 12 to 19 years ( M = 15.4, SD = 1.84), in Hong Kong. Results indicated that a modified five-factor model had a better overall fit to the data than the five-factor model reported by Pintrich and De Groot in a sample of junior high school stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
0
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 13 publications
9
61
0
6
Order By: Relevance
“…Therefore, these four items were discarded, and only the academic self-efficacy factor was used during further analyses. Note that Rao and Sachs (1999) have already recognized that Chinese respondents may have trouble answering reverse-coded items. The present study confirmed that Chinese students indeed have such difficulties (see also Rao et al, 2000;Sachs et al, 2001).…”
Section: Data Analysesmentioning
confidence: 99%
“…Therefore, these four items were discarded, and only the academic self-efficacy factor was used during further analyses. Note that Rao and Sachs (1999) have already recognized that Chinese respondents may have trouble answering reverse-coded items. The present study confirmed that Chinese students indeed have such difficulties (see also Rao et al, 2000;Sachs et al, 2001).…”
Section: Data Analysesmentioning
confidence: 99%
“…Rao and Sachs (1999) found that these items formed a separate "Methods" scale, which reflected difficulties Chinese respondents had in dealing with reverse-coded items. We also found a separate "Methods" scale and excluded these items from further analysis.…”
Section: Instrumentsmentioning
confidence: 99%
“…It is another method to conceptualize goodness of fit by comparing an existing model with a null model which assumes the latent variables in the model are uncorrelated (Tabachnick & Fidell, 2007;Johnson et al, 2007). The RMSEA is similar to the RMR, but it assesses the discrepancy between the model implied covariance (correlation) matrix and the observed covariance (correlation) matrix by taking into account the degree of freedom or number of free parameters required to achieve a given level of fit (Rao & Sachs, 1999). Practitioners and statistical experts have different thresholds for RMSEA but most salient ideas are that the value of RMSEA must between .05 and .08 and between .05 and 1.00 (Rao & Sach, 1999;Hulpia et al, 2009;Cadiz et al, 2009).…”
Section: Results and Discussion Of Measurement Modelmentioning
confidence: 99%